(untitled) (Research, Society and Development, 2022)
This study aimed to review the literature on the identification of impacts on the physical health of the elderly caused by social isolation during the COVID-19 pandemic. This is an integrative literature review, carried out using a search strategy in the Latin American and Caribbean Literature on Health Sciences (LILACS via VHL), SciVerse Scopus, Web of Science, PubMed and Science Direct databases, through the health descriptors "older adults", "motor activity" and "COVID-19" and according to previous readings on the topic of interest. Twenty-five studies were included, published from the year 2020 in English, Spanish or Portuguese, which met the adopted inclusion and exclusion criteria and addressed the repercussions of social isolation on the physical health of the elderly in different regions of the world. From the restriction and isolation measures adopted to contain the contagion of the SARS-CoV-2 virus, one can observe repercussions on the psychological and physical well-being of the elderly. The interruptions of physical, recreational, and daily needs activities during the pandemic period had repercussions on the increased incidence of frailty, sedentarism, and malnutrition, which consequently negatively affect the psychosocial relationships of these individuals by elevating depressive and anxiety symptoms.